The Reality and Motives of Adherence to Information Security Policies in Palestinian Higher Education Institutions: A Case Study of Hebron University - Belal Amro (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
Information systems security is a core factor in the development and using of computer information systems which provides security for the data and privacy for users; and humans are one of the major key players in this field. Some of human behaviors that leads to security breaches in computer information systems include Ignorance, negligence, indifference, and lack of awareness in information security. In this research, we are spotting the light on the importance of information system security policies in higher educational institutions in Palestine - Hebron University case study. The importance of this research lies in knowing the reality of information systems security policies in Palestinian universities and knowing the factors affecting adherence to information security policies such as knowledge of information security, experience, and educational level. The study concluded that the degree of knowledge about the security of information systems and their adherence by the staff of Hebron University was high. The study also concluded that there are statistically significant differences related to the staff adherence to information systems security policies according to the educational level and experience. The study has recommended the necessity of following up the implementation of information systems security policies, and updating and reviewing them in line with the requirements of the next phase and the tremendous technological development the world is witnessing.